2019
DOI: 10.1007/s12542-019-00486-7
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo leaf cuticle chemistry across changing pCO2 regimes

Abstract: Cuticles have been a key part of palaeobotanical research since the mid-19th Century. Recently, cuticular research has moved beyond morphological traits to incorporate the chemical signature of modern and fossil cuticles, with the aim of using this as a taxonomic and classification tool. For this approach to work cuticle chemistry would have to maintain a strong taxonomic signal, with a limited input from the ambient environment in which the plant grew. Here, we use attenuated total reflectance Fourier Transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The question concerning the influence of pCO 2 on cuticle chemistry remains unresolved. A recent study by Jardine et al (2019) addressed this issue via a meticulous experiment to test for the effects of pCO 2 variations on Ginkgo biloba leaf cuticle chemistry. By using attenuated total reflectance Fourier transform IR spectroscopy on leaves from plants grown in chambers with enhanced pCO 2 conditions, they showed that pCO 2 had little effect on the cuticle chemistry (Jardine et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The question concerning the influence of pCO 2 on cuticle chemistry remains unresolved. A recent study by Jardine et al (2019) addressed this issue via a meticulous experiment to test for the effects of pCO 2 variations on Ginkgo biloba leaf cuticle chemistry. By using attenuated total reflectance Fourier transform IR spectroscopy on leaves from plants grown in chambers with enhanced pCO 2 conditions, they showed that pCO 2 had little effect on the cuticle chemistry (Jardine et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Jardine et al (2019) addressed this issue via a meticulous experiment to test for the effects of pCO 2 variations on Ginkgo biloba leaf cuticle chemistry. By using attenuated total reflectance Fourier transform IR spectroscopy on leaves from plants grown in chambers with enhanced pCO 2 conditions, they showed that pCO 2 had little effect on the cuticle chemistry (Jardine et al 2019). However, an experiment with limited short-term elevated pCO 2 in growth chambers may not accurately reflect the influence on Ginkgoales cuticle in the past, such as in the Mesozoic greenhouse world, when plants were both adapted to and grew naturally over many generations under highly elevated pCO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2j); these analyses yield chemo‐ecological data in relation to plant–insect interactions via chemical signaling to pollinators, seed dispersers, and prey and on secondary metabolites defense against UV‐B radiation (reviewed in García‐Plazaola et al ., 2015; Leide et al ., 2020). For example, strong autofluorescence in the blue (emission at 475 nm) under excitation with UV light (360 nm) can signal the presence of UV‐protecting compounds such as coumarin (García‐Plazaola et al ., 2015; Jardine et al ., 2019).…”
Section: Fossil Leaf Functional Traitsmentioning
confidence: 99%